Research Progress of Heavy Metals in Marine Environment and Organisms of Beibu Gulf in Guangxi - WANG Yi; LI Shi (Renmin Zhujiang)
In order to understand the situation of heavy metal pollution of Beibu Gulf in Guangxi,this paper collects the relevant research results of seven heavy metals in seawater, sediments andorganisms of Beibu Gulf in Guangxi in recent years, compares and analyzes the pollution level andspatial distribution of heavy metals in seawater and sediments, discusses the pollution level,enrichment and accumulation of heavy metals in organisms, and finally assesses the pollution ofseven heavy metals in seawater, sediments and organisms.The results show that:①In seawater, theconcentrations of Cu、Zn、Cd、Cr and As are up to the Class I marine water quality standards. Andcompared with other sea areas in our country, the heavy metals are overall at high levels, whichall meet water quality standards for fisheries except Hg; ②Compared with other sea areas in ourcountry, the heavy metals in sediments are generally at low levels, which are all up to the ClassI marine sediment quality standards. And according to Hakanson's potential ecological riskassessment results, Zn、Cr、Pb、Cu、As and Hg all belong to low ecological risked types, the orderof the potential ecological risk indexes of heavy metals is: Cd＞Hg＞As＞Pb＞Cu＞Zn＞Cr, and thecomprehensive potential ecological risk indexes of the heavy metals are all less than 150 in thesea areas of Qinzhou, Beihai and Fangchenggang, which present low ecological risk; ③The heavymetals in organisms meet the Class II standard of marine biological quality basically, however,the concentrations of Cd,Cu and Pb are more than national food and health standard; ④Thebioaccumulation and accumulation ability of heavy metals is different in different organisms. Themarine environment and organisms have been polluted by heavy metals to a certain extent. Atpresent, we should adopt the strategy of combining prevention and treatment in time, and avoidpollution before treatment.